HUBUNGAN POLA ASUH ORANG TUA DENGAN KEBERHASILAN TOILET LEARNING PADA ANAK USIA TODDLER DI RW 02 DAN RW 06 KELURAHAN TLOGOMAS MALANG - Ela Ela; Roni Yuliwar; Novita Dewi (Care : Jurnal Ilmiah Ilmu Kesehatan, 2014)
The successful of toilet learning is the child's ability to control the pattern of elimination as well as learning to use the toilet properly. The purpose of this study was to analyze the relationship between parenting with successful of toilet learning for the children of toddler age in RW 02 and RW 06 Village of Tlogomas Malang Year 2013. This research design is descriptive correlation. Total population: 65 people with cross sectional approach using purposive sampling technique. The number of samples 40 parents who have the children of toddler age and 40 children of toddler age. This study was conducted in July 2013. Research uses the chi square test. From the results of study showed 31 (77.5%) included in the democratic category, while for the successful of toilet learning for the children of toddler age in success category as many as 31 people (77.5%). The result of statistical test is known the p value 0.000 < 0.05 means that H0 is rejected, H1 was accepted means there is a significant relationship between parenting with the successful of toilet learning for the children of toddler age in RW 02 and RW 06 Village of Tlogomas Malang. It is suggested for the parents to apply the good (suitable) parenting so the children do not experience the late (delaying) in development especially toilet learning. For the further research, researcher recommend to study the factors that affect the successful of toilet learning for the children of toddler age